Harpies in the House: Neo-Victorian Rewritings of Avian Femininities - Contreras Ameduri, Clara (Complutense Journal of English Studies, 2024)
This article examines avian metaphors in Neo-Victorian literature in relation to contemporary reconsiderations of nineteenth-century womanhood and its connection to animal discourse. Ornithological imagery and the female condition were closely linked in the nineteenth-century cultural imaginary, as clearly manifested in the period’s literature and art. From the idealized image of the submissive wife caged within the Victorian household to the controversial use of feathers in feminine accessories, bird-like women perched on the margins between the domestic space and the outside world. Significantly, birdcage imagery has since been recovered by numerous feminist authors to denounce women’s lack of freedom under patriarchal oppression. However, such analogies have often been rooted in a rejection of animality, rather than in a sense of solidarity between women and animals against androcentric domination. As this article intends to prove, Neo-Victorian works such as A. S. Byatt’s The Conjugial Angel (1992) and Angela Carter’s Nights at the Circus (1984) offer subversive possibilities for the reinterpretation of avian imagery in ways that challenge the interlocking patriarchal and speciesist dynamics at the core of anthropocentric culture.